Enhancing Financial Capability and Inclusion in Mozambique : A Demand-Side Assessment - World Bank Group (Washington, DC, 2014)
The key findings and recommendations presented in this report cover 4 main areas: financial inclusion, financial capability, relationship between financial inclusion and capability, and financial consumer protection. The remaining chapters are structured as follows. Chapter one explores the financial inclusion landscape in Mozambique. Chapter two gives an overview of Mozambicans' levels of financial capability, in particular about their financial knowledge, attitudes and behaviors. The relationship between financial capability and inclusion is discussed in chapter three. The last chapter investigates if the products which financially included individuals use are effectively meeting their needs.